Analisis Hambatan Samping Pada Segmen Jalan Yos Sudarso Akibat Adanya Kegiatan Di Pusat Perbelanjaan Lippo Plaza: Analysis Of Side Friction On Yos Sudarso Road Segment Due To Activities At Lippo Plaza Shopping Center - Noviantama, Aldy; Riani, Desi; Robby, Robby (Media Ilmiah Teknik Sipil, 2025)
The segment of Jalan Yos Sudarso is designated as a shopping area. The largest shopping center on Jalan Yos Sudarso is Lippo Plaza. Activities at Lippo Plaza are frequented by many residents of Palangka Raya City. This condition affects the level of traffic congestion caused by the significant movement of vehicles to and from Lippo Plaza, which includes traffic volume, side obstacles, and vehicle speed. This study aims to discuss the impact of activities at the Lippo Plaza shopping center on the performance of the road segment on Yos Sudarso Street in Palangka Raya City, including the average daily traffic volume, average side friction, instantaneous vehicle speed, and vehicle maneuvering time at U-turns using the Indonesian Road Capacity Guidelines 2023. From the research results, the peak traffic volume was obtained at 1,346.30 smp/hour in Direction A-A, and 1,503.10 smp/hour in Direction B-B. The peak side friction obtained was 1,852.80 incidents/hour in Direction A-A with a classification of "Very High" and 410.70 incidents/hour in Direction B-B with a classification of "Moderate." The saturation degree values obtained were 0.48 in Direction A-A and 0.49 in Direction B-B, with the service level classification for both directions being "C."